Dynamic mechanical properties of activated carbon–filled epoxy nanocomposites. - Abdul Khalil, H. P. S.; Jawaid, Mohammad; Firoozian, Parisha; Zainudin, Edi Syams; Md. Tahir, Paridah (Taylor & Francis, 2013)
Nano-activated carbons obtained from oil palm empty fiber bunch (AC-EFB), bamboo stem (AC-BS), and coconut shells (AC-CNS) were reinforced in epoxy matrix to fabricate epoxy nanocomposites. The dynamic mechanical analysis of epoxy nanocomposites was carried out, and 5% AC-CNS treated with KOH-filled epoxy composites displayed the highest storage modulus of all the activated carbon–filled epoxy composites. The incorporation of a small amount of AC-BS, AC-EFB, and AC-CNS to the epoxy matrix enhanced the damping characteristics of the epoxy nanocomposites. The 5% AC-EFB treated with H3PO4 filled epoxy composites showed the highest glass transition temperature (Tg) in all temperature ranges.